Pengaruh Total Asset Turnover (TATO), Debt To Equity Ratio (DER) Dan Current Ratio (CR) Terhadap Pertumbuhan Laba PT. Baramulti Suksessarana Tbk. - Rostinah Rostinah; Aliah Pratiwi; Nurhayati Nurhayati; ST. Asytah (JURNAL DIMENSI, 2026)
This study aims to analyze the effect of Total Asset Turnover (TATO), Debt to Equity Ratio (DER), and Current Ratio (CR) on profit growth at PT Baramulti Suksessarana Tbk. This study uses a quantitative method with an associative research type. The data used are secondary data in the form of company financial reports for the period 2015–2024 obtained through documentation from the company's financial reports. Data analysis techniques used include classical assumption tests, multiple linear regression analysis, coefficient of determination, correlation coefficient tests, t-tests, and f-tests with the help of the SPSS version 25 program. The results of the study indicate that partially Total Asset Turnover (TATO) does not affect profit growth with a calculated t value of -1.662 and a significance value of 0.147 > 0.05. Debt to Equity Ratio (DER) also does not affect profit growth with a calculated t value of 1.683 and a significance value of 0.143 > 0.05. Furthermore, Current Ratio (CR) does not affect profit growth with a calculated t value of 0.277 and a significance value of 0.791 > 0.05. Simultaneously, TATO, DER, and CR do not affect profit growth with a calculated F value of 1.684 < F table 4.10 and a significance value of 0.269 > 0.05. Thus, it can be concluded that Total Asset Turnover, Debt to Equity Ratio, and Current Ratio have not been able to become the main factors influencing profit growth at PT Baramulti Suksessarana Tbk.